Primary subcutaneous extra skeletal Ewing’s sarcoma: a case report on a very rare clinical entity - Ahire, Priya P.; Nichat, Pramod D.; Ansari, Kashif F.; K. B., Vismaya; Parmar, Kuldeep; Mohanraj, Aishwarya; Kadam, Akshay V.; Yadav, Subhash (International Surgery Journal, 2021)
Primary extra skeletal Ewing’s sarcoma is a very rare clinical entity. Patients are normally females in the second decade of their life. Clinically it normally presents as a fleshy mass which is mobile, not attached to the underlying structures. Diagnosis is difficult, final diagnosis being made by histopatholoical, immunohistochemistry and cytoskeletal studies combined. Ewing’s sarcoma is a tumour which normally affects the bones, and to a much lesser extent (10%) the soft tissues. Primary extra skeletal Ewing’s sarcoma affecting the back (as in the case we are discussing) is an extremely rare clinical entity with lesser than 50 cases reported worldwide. The entity being so rare doesn’t have any much literature for review.